(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Porras-Murillo LP, Wong G, Chacón IS. 2022. Human-wildlife interactions in a major tourist destination: Manuel Antonio National Park, Costa Rica. Biodiversitas 23: 2417-2425. This study characterized the interactions between tourists and wildlife in terms of the most common interactions and the species that interact the most. Interactions were observed during 65 sampling days between 2012 and 2020. In each event, the following data were recorded: date, time (hour), site, type of interaction, and species that participated. To characterize the interactions, the effects of the day of the week, the season, the daily period, and the site on the number of daily interactions were evaluated. Also, to understand the more frequent interactions, the effect of species and type of interaction on ??the number of daily interactions were evaluated. The results indicated more interactions in the dry season, between 10 am and 2 pm, at Manuel Antonio Beach, Costa Rica. Although interactions were recorded for 39 species, white-faced monkey and raccoon were the species with the most interactions. Raccoons had more interactions related to food than the tourists called or approached them; white-faced monkeys had a similar number of interactions in these categories. Interactions between tourists and wildlife in the Manuel Antonio National Park (PNMA), Costa Rica, coincide with the times and places in the park with the highest concentration of tourists. Therefore, there is evidence of the need to promote tourism with appropriate behavior of observation and respectful appreciation of wildlife, and the use of more sectors of the park is essential to avoid damage to fauna.